Data on Emission Factors of Gaseous Emissions from Combustion of Woody Biomasses as Potential Fuels for Firing Thermal Power Plants in Nigeria - Francis Boluwaji Elehinafe; Oyetunji Babatunde Okedere; Queen Edidiong Ebong-Bassey; Jacob Ademola Sonibare (Universitas Muhammadiyah Magelang, 2021)
This work generated data on the emission factors of air emissions from combustion of woody biomasses collected from southwest, Nigeria. This was with a view to finding their potentials as sustainable and environmentally friendly fuels for firing thermal power plants compared to coals. The data on heating values and elemental contents (carbon, sulphur and nitrogen) responsible for gaseous emissions in the 100 woody biomasses were collected from the previous results of this work to determine the gaseous emission factors on the expected condition of complete combustion. The current results showed that the CO2 emission factors ranged from 0.0147 kg/(MJ/kg) for Ficus mucuso to 0.1499 kg/(MJ/kg) for Spondias mombin, SO2 emission factors ranged from 0.0000000 kg/(MJ/kg) for Pterygota macrocarpa, Irvingia grandifolia, and fifteen others, to 0.0011341kg/(MJ/kg) for Khaya ivorensis, while NO2 emission factors ranged from 0.0000000 kg/(MJ/kg) for Citrus medica to 0.0035824 kg/(MJ/kg) for Ficus carica. Considering the minimal emissions from biomasses compared to coal species, serious political will is needed on the part of the Nigerian government to propagate these biomasses for fuels in firing the thermal plants in the country.